A Parallel Study of mRNA and microRNA Profiling of Peripheral Blood in Young Adult Women - Sredni, Simone T.; Gadd, Samantha; Jafari, Nadereh; Huang, Chiang-Ching (Frontiers in Genetics, 2011)
Backgound: Aging is a complex process that involves the interplay of genetic, epigenetic, and environmental factors. Identifying aging-related biomarkers holds great potential for improving our understanding of complex physiological changes, thereby providing a means to investigate the mechanism by which aging influences various diseases. Method and Results: We performed a parallel study of microRNA and gene expression profiling of peripheral blood in a group of healthy young adult women, among which 13 were aged 22-25 and 9 were aged 36-39 years old. We identified a significantly distinct pattern of microRNA, but not gene expression profiling, between these two young adult women groups. We also performed correlation analysis of expression levels between all pairs of age-associated microRNAs and genes and identified a weak global correlation between these two types of expression levels. A significant involvement of estrogen regulation was observed by pathway analysis of the most differentially expressed microRNAs that included miR-155, -18a, -142, -340, -363, -195, and -24. Conclusion: Our results suggest that the change in global microRNA expression in the peripheral blood is associated with normal aging in young adult women. This change may precede global gene expression changes. Future study is needed to investigate the regulatory mechanism of the estrogen-related microRNAs and associated diseases.